Three-phase voltage dips in load nodes of the electrical network of the Santiago de Cuba province measure for its correction - José Ricardo Nuñez-Alvarez; Janette Cervantes-Oliva; Ramon Antonio Zambrano-Mero; Hernan Hernández-Herrer; Yolanda Llosas-Albuerne (Institute of Advanced Engineering and Science, 2026)
The growing need to supply quality electrical energy to end-users has given rise to various studies and research on the technical parameters that this energy should possess. In addition, many users perceive that many of the problems in the operation of their household appliances are related to the quality of the electrical energy that reaches their homes. One of the fundamental problems affecting the quality of electrical power is the so called voltage dips, which are nothing more than disturbances of great relevance due to their direct consequences, secondary effects, and frequency of occurrence. In this research, a study is conducted to evaluate the occurrence of three-phase voltage dips in a simplified electrical network in Santiago de Cuba, Cuba. As a result, the Santiago Norte substation presents the most detrimental behavior. In addition, 50% of the simulations performed on the behavior of the Santiago East Substation, which handles a voltage of 13.8 kV, showed that it is the substation where the deepest voltage dips occur. Based on the results obtained, it has been decided to change the transformer tapping of the affected substations to reduce the occurrence of voltage dips and ensure stable operation in the event of three phase faults in the power system under analysis.